Feeling Good or Doing Good: Inefficacy of the U.S. Unilateral Sanctions Against the Military Government of Burma/Myanmar - Thihan Myo Nyun (Washington University Global Studies Law Review, 2008)
Part I of the Article presents a general overview of the use of sanctions as economic statecraft. Part II frames the U.S. unilateral sanctions policy analysis in the Burmese context. Part III of the Article begins the analysis of the political and economic variables that are regularly implicated in determining whether sanctions are likely to succeed. In Part IV, I suggest additional legal, social, and humanitarian variables that might better approximate the efficacy of the sanctions when considered in an episode-specific manner.
Keywords: Human rights – Burma; Military government; Economic sanctions – Burma; Burma – Foreign relations; United States – Foreign relations; Sanctions (International law); International; Myanmar